Restorative Justice Policy Analysis in Eradicating Corruption - Hamzah, Andi (UNISSULA Semarang, 2025)
This study analyzes the application of the principle of restorative justice (RJ) in eradicating corruption in Indonesia, both in the context of current law (ius constitutum) and for the development of future policies (ius constituendum). Through a normative legal approach, this study identifies conflicts of norms and legal principles that hinder the implementation of restorative justice and offers normative solutions to overcome them. The results of the study indicate that the current application of restorative justice is still limited by the retributive legal framework, lack of coordination between institutions, and community resistance. However, restorative justice has the potential to complement the retributive approach by emphasizing the restoration of state losses and social reconciliation. This study recommends a revision of the Corruption Law, the preparation of implementing regulations, and public education to support a more effective implementation of restorative justice.